PEMASARAN BUAH STROBERI DARI KELURAHAN RURUKAN DAN RURUKAN SATU KECAMATAN TOMOHON TIMUR, KOTA TOMOHON - Trisari B. Dj. Kodobik; Agnes E. Loho; Joachim N. K. Dumais (AGRI-SOSIOEKONOMI, 2017)
This study aims to find out the marketing channels of strawberries ranging from farmers in the Village Rurukan and Rurukan one to the supermarket. The research was conducted in Kelurahan Rurukan and Rurukan Satu East Tomohon Subdistrict Tomohon City for three months from May 2016 until July 2016. The data obtained are primary and secondary data. Primary data is data sourced from direct interviews with related parties, among others strawberry farmers who became the subject of research. Secondary data is data obtained by the researcher who sourced from documents from related agencies, such as: Rurukan urban village office and Rurukan Satu East Tomohon subdistrict Tomohon City, internet and library sources or literature book data is analyzed by using marketing margin, farmer's share and profit margin. Based on the results of marketing channel research as much as two channels of marketing channel I ranging from farmers to final consumers, marketing channels II farmers to the Supermarket divided into two places namely Cool Tomohon and Freshmart Bahu. The result of marketing Margin of strawberry fruit on channel I is Rp. 0 (0%). For marketing margin value II is Rp. 6500 (30, 23%) (Cool) and Rp. 13,000 (46, 42%) (Freshmart). This shows that the largest margin of marketing value occurs in the marketing channel II in the supermarket Freshmart. The largest profit margin in the strawberry fruit sequence that occurs in marketing channel I between farmers to consumers with profit margin of Rp. 13,250 (98.14%).*jnkd*